Bacterium-Like Particles Displaying the Rift Valley Fever Virus Gn Head Protein Induces Efficacious Immune Responses in Immunized Mice - Zhang, Shengnan; Yan, Feihu; Liu, Dongping; Li, Entao; Feng, Na; Xu, Shengnan; Wang, Hualei; Gao, Yuwei; Yang, Songtao; Zhao, Yongkun; Xia, Xianzhu (Frontiers in Microbiology, 2022)
Rift Valley fever virus (RVFV), a mosquito-borne zoonotic phlebovirus, causes serious disease in humans and ruminants. According to the World Health Organization, Rift Valley fever is classified as a priority disease, and as such, vaccine development is of high priority due to the lack of licensed vaccines. In this study, a bacterium-like particle vaccine (BLP), RVFV-BLPs, is constructed. A novel display system is described, which is based on non-living and non-genetically modified Gram-positive bacterial cells, designated as Gram-positive enhancer matrix (GEM). The RVFV Gn head protein was displayed on the surface of GEM by co-expression with the peptidoglycan-binding domain (protein anchor) at the C-terminus. We determined that the RVFV Gn head-PA fusion protein was successfully displayed on the GEM. Mice immunized with RVFV-BLPs produced humoral and cellular immunity. Interestingly, comparing the production of RVFV Gn head-specific IgG and its subtype by vaccinating with different antigen doses of the RVFV-BLPs determined that the RVFV-BLPs (50 μg) group showed a greater effect than the other two groups. More importantly, antibodies produced by mice immunized with RVFV-BLPs (50 μg) exhibited potent neutralizing activity against RVFV pseudovirus. RVFV-BLPs (50 μg) also could induce IFN-γ and IL-4 in immunized mice; these mice generated memory cells among the proliferating T cell population after immunization with RVFV-BLPs with effector memory T cells as the major population, which means that RVFV-BLPs is an effective vaccine to establish a long-lived population of memory T cells. The findings suggest that the novel RVFV-BLPs subunit vaccine has the potential to be considered a safe and effective candidate vaccine against RVFV infection.